The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1186/1471-2164-9-603
|View full text |Cite
|
Sign up to set email alerts
|

High quality draft sequences for prokaryotic genomes using a mix of new sequencing technologies

Abstract: Background: Massively parallel DNA sequencing instruments are enabling the decoding of whole genomes at significantly lower cost and higher throughput than classical Sanger technology. Each of these technologies have been estimated to yield assemblies with more problematic features than the standard method. These problems are of a different nature depending on the techniques used. So, an appropriate mix of technologies may help resolve most difficulties, and eventually provide assemblies of high quality withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 26 publications
0
62
0
1
Order By: Relevance
“…The cumulative scaffold size was 472.2 Mb, about 10% smaller than the estimated genome size of 523 Mb. Sequence quality of scaffolds from the Newbler assembly was improved as described previously 34 , by automatic error corrections with Solexa/Illumina reads (50-fold genome coverage), which have a different bias in error type compared with 454 reads. To validate the assembly, we built a unigene set corresponding to 15,017 isotigs that were obtained from the assembly with Newbler (version MapAsmResearch-03/15/2010) of Roche/454 GSFLX reads from six different complementary DNA (cDNA) libraries (829,587 reads, Supplementary Text).…”
Section: Methodsmentioning
confidence: 99%
“…The cumulative scaffold size was 472.2 Mb, about 10% smaller than the estimated genome size of 523 Mb. Sequence quality of scaffolds from the Newbler assembly was improved as described previously 34 , by automatic error corrections with Solexa/Illumina reads (50-fold genome coverage), which have a different bias in error type compared with 454 reads. To validate the assembly, we built a unigene set corresponding to 15,017 isotigs that were obtained from the assembly with Newbler (version MapAsmResearch-03/15/2010) of Roche/454 GSFLX reads from six different complementary DNA (cDNA) libraries (829,587 reads, Supplementary Text).…”
Section: Methodsmentioning
confidence: 99%
“…The Illumina reads are then projected or mapped onto the 454 scaffold and can be used to correct the errors in homopolymeric runs. In this way it is possible to circumvent the use of expensive Sanger sequencing (Aury, et al, 2008).…”
Section: Generation Of Improved High-quality Draft Genome Sequencesmentioning
confidence: 99%
“…A later study (Aury, et al, 2008) investigated the combination of Sanger, pyro-and Illumina sequencing. They found that with paired-end 454 technology and Illumina sequencing a Sanger sequencing run is dispensible.…”
Section: Generation Of Improved High-quality Draft Genome Sequencesmentioning
confidence: 99%
“…Given the dual approach to sequencing these genomes, this suggests that these variations maybe genuine and that C. difficile may using 454 sequencing technology, which can introduce errors in homopolymeric tracts this sequence data was confirmed using Solexa sequencing technology, which usually negates the problems associated with 454 sequencing technology. 16 Furthermore, seven of the frame shifts 11 Red bars indicate ≥99% homology between R20291 and CD196 DNA sequence. 630 Cdi1 was in the same orientation as R20291.…”
mentioning
confidence: 99%